Research on the Temperature Characteristics of 1 200 V 4H-SiC Junction Barrier Schottky Diode - YUAN Hao; SONG Qingwen; TANG Xiaoyan; YUAN Lei; ZHANG Yimen; ZHANG Yuming (Kongzhi Yu Xinxi Jishu)
In order to research the effect of temperature on static electrical parameters of 4H–SiC junction barrier Schottky (JBS) diode,1.2 kV 4H–SiC JBS diodes were fabricated and their current-voltage characteristics were measured in the range of 25 ℃ ~150 ℃ . The results illustrate the forward current is 5 A at room temperature with forward voltage drop of 1.5 V and its breakdown voltage can reach to 1 300 V at least, illustrate a good static I-V characteristic. Meanwhile, the fabricated device can work normally under high temperature (150 ℃ ), and the schottky height and ideal factor remain unchanged with temperature increasing, thus it has good stability. However, its onresistance increases with temperature rising due to the decreasing of mobility of carrier, which shows positive temperature coefficient. At reverse bias, breakdown voltage does not degrade as temperature rising. Reverse leakage current rises by almost 1.5 orders of magnitude at low reverse voltage comparing to the reverse leakage current at room temperature and rises by only 1order of magnitude at high reverse voltage with temperature increasing, which is in accord with avalanche breakdown mechanism.